Theorising on tourist flows and business cycles in casino cities - Sheng, Li; Yin, Yechang; Zhang, Anning (Publishing House of Wroclaw University of Economics and Business, 2022)
Two models of gambling destinations were developed to illustrate how external shocks from tourist origin countries are spread via tourist flows into destinations. Theorising on such mechanisms made it possible to simulate the driving forces behind business cycles and offer a theoretical construct for numerical analysis. It was found that favourable changes in push and pull factors can create a sound environment of lower prices, more tourism and growing income.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 187-199
Keywords: push factors; pull factors; business cycles; visitor flows